Prospects for a Rim County Population Rebound: Can Quality of Place Lure In-Migrants? - Vail, David (Maine Policy Review, 2010)
David Vail asks whether population will rebound in Maine’s rural “rim” counties and whether investing to enhance “quality of place” can attract large numbers of rural settlers. Review of the evidence suggests that Maine’s rim counties are not experiencing a population rebound and that rural counties vary greatly in their ability to hold onto existing residents or attract new ones. Vail argues that quality-of-place investments should not be considered as a core development tool for rural areas, but that they can complement traditional rural economic policy measures. Since it is difficult to stimulate a major population movement to Maine’s rim counties, amenity investments should focus on enhancing quality of life for current residents, thereby strengthening their incentive to stay.